ETUDE DES FACTEURS D’OPTIMISATION DE LA VENTE DANS UNE ENTREPRISE TABACICOLE : « CAS DE LA GLOBAL MARKET MOVERS SARL » - Castro, MBULA ABDI (IJRDO - Journal of Business Management, 2021)
The present research focuses on the study of the factors of sales optimization in a tobacco company. The reasons for undertaking this study were to identify and analyze the explanatory factors of the optimization of the sale in the commercial company in general and in a tobacco company in particular, in order to highlight their influence in the optimization of the productivity of this one and to have an idea on the evolution of the sales of this company in order to release the gaps which exists between the realized turnover compared to the various expenses related to the marketing and the distributionThe results of this study proved that the factors of optimization of the sale of the GMM/Isiro would be the implementation of an effective marketing policy which would bring the product closer to the consumers and a good management of its sales force by starting with the recruitment, the training, the remuneration, the animation, the control and the evaluation. The correlation coefficient is 0.4873 > 0 : therefore there is a presumption of a positive correlation between turnover (Yt) and marketing expenses (X_t), i.e. the two variables move in the same direction : if marketing expenses increase, turnover also increases and if marketing expenses decrease, turnover also decreases ; the coefficient of determination is 0. 2375 i.e. the model is globally explained at 23.75 % by the endogenous variable (the turnover) which depends on the exogenous variable (the marketing expenses); in other words on the 100% of the sales realized by the GMM, 23.75 % are realized according to the marketing expenses The remaining 76.25% are explained by other variables than marketing expenses such as preference, price, taste, environment, product availability or permanence, agent motivation, habit, etc.